The Use of Minimal Pairs to Improve Pronunciation of the Tenth Grade Students of SMA Negeri 2 Sigi - Mentari, Cindhy Qirana Cinta; Rofiqoh, Rofiqoh; Hastini, Hastini; Kamaruddin, Abd. (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to prove whether the use of minimal pairs can improve pronunciation of fricative sounds of the tenth grade students of SMA Negeri 2 Sigi. This research used a pre experimental design. The population of this research was 266 tenth grade students of SMA Negeri 2 Sigi. The sample was selected by employing a purposive sampling technique. The sample was 34 students of Class XC. To collect the data, a pronunciation test was used as the research instrument. The data were analyzed using SPSS 30. The findings revealed that the students’ pronunciation improve after getting the treatment. Based on the calculation, the mean score of posttest (72.73) is higher than the mean score of pre-test (43.07). It is supported by the data analysis using paired sample t-test. It showed that the value of Sig.(2-tailed) is lower than the chosen alpha level (0.000 0.05). Therefore, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be concluded that the use of minimal pairs can improve pronunciation of the tenth grade students of SMA Negeri 2 Sigi. The implication of the finding to the teaching practice is that the teachers need to use minimal pairs in teaching pronunciation to make students’ pronunciation better.